Pedagogy of Discomfort as a Project of Citizenship Education: About Commitment to Social Justice from the Perspective of the Feminist Theories of Emotions - Góralska, Renata (Przegląd Badań Edukacyjnych (Educational Studies Review), 2023)
The aim of the article is to describe the assumptions of the ‘pedagogy of discomfort’ and to analyse its main theses from the perspective of its potential perception as a pedagogical ‘project’ of citizenship education. The theoretical context is provided by the feminist theories of emotions (e.g. by Megan Boler, Rosi Braidotti and Martha Nussbaum), which emphasise the importance of educational activities for social justice and the affective and ethical dimension of citizenship education. The research problem of the article is focused around two questions: (1) what are the goals and assumptions of the pedagogy of discomfort and (2) what is the pedagogical potential of pedagogy of discomfort from the perspective of socially and democratically oriented citizenship education. The research was embedded in the paradigm of humanistic- oriented pedagogy and the research method used is a qualitative, thematic analysis of the sources selected for the sample, i.e. six original and co-authored texts by Megan Boler – the author of the concept of ‘pedagogy of discomfort.’ The research results indicate that feminist theories of emotions, including Megan Boler’s philosophy of education known as the ‘pedagogy of discomfort,’ carry implications that are important for pedagogical actions for social justice, democracy and the common good.